2009
DOI: 10.1038/nnano.2008.406
|View full text |Cite
|
Sign up to set email alerts
|

Large voltage-induced magnetic anisotropy change in a few atomic layers of iron

Abstract: In the field of spintronics, researchers have manipulated magnetization using spin-polarized currents. Another option is to use a voltage-induced symmetry change in a ferromagnetic material to cause changes in magnetization or in magnetic anisotropy. However, a significant improvement in efficiency is needed before this approach can be used in memory devices with ultralow power consumption. Here, we show that a relatively small electric field (less than 100 mV nm(-1)) can cause a large change (approximately 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

39
982
8
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,242 publications
(1,042 citation statements)
references
References 27 publications
39
982
8
1
Order By: Relevance
“…In ultrathin FePt films, they found a change of the coercivity of 4.5 % under the application of electric 1 Introduction fields. A Japanese group found large changes in the anisotropy of magnetic thin films in TMR junctions under application of high electric fields [12]. A bistable toggle switching of the magnetization direction between two bistable orientations has been reported very recently by the same group [13].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In ultrathin FePt films, they found a change of the coercivity of 4.5 % under the application of electric 1 Introduction fields. A Japanese group found large changes in the anisotropy of magnetic thin films in TMR junctions under application of high electric fields [12]. A bistable toggle switching of the magnetization direction between two bistable orientations has been reported very recently by the same group [13].…”
Section: Introductionmentioning
confidence: 95%
“…It was claimed that the electric field changed the number of unpaired d-electrons in the surface and thus affected the magnetic properties. The next step towards a possible application of MEC in high-efficiency memory devices was made in the group of Y. Suzuki: a change of the magnetic anisotropy by 40 % induced by an electric field in a Fe/MgO junction was observed in 2009 by Maruyama et al [12] (see Fig. 2.6b)).…”
Section: Magnetoelectric Couplingmentioning
confidence: 99%
“…7) or an electric field can modify antiferromagnetic order (BiFeO 3 ) [8][9][10] . There are few ferromagnetic piezoelectric materials 11 in which to attempt voltage-driven changes in magnetization, but the magnetization of thin ferromagnetic films may be electrically modified via strain from piezoelectric substrates (BaTiO 3 19 ; or via the occupation of 3d orbitals in ultra-thin Fe films 20 .…”
Section: Between Ferroelectricmentioning
confidence: 99%
“…Demonstrating electrical control of coercivity 19,24 , exchange bias 25,26 or magnetic anisotropy 20,27 is insufficient because, respectively, an electrically addressable coercivity is inextricably linked with an applied magnetic field; because exchange bias is an interfacial phenomenon that cannot readily drive magnetization reversal throughout a film of significant thickness; and because no new magnetic anisotropy axis can lie more than 901 from the anisotropy axis along which the local magnetization initially lies. It has been suggested that this latter challenge may be overcome by applying a suitable sequence of normal stresses near the pre-existing magnetic anisotropy axes of a small homogeneously magnetized Stoner-Wohlfarth particle 28,29 , but this has not been experimentally realised.…”
Section: Between Ferroelectricmentioning
confidence: 99%
“…11 A strong effect of applied electric field on the interface MCA was demonstrated for the Fe/MgO (001) interfaces. 12 Magnetic easy axis manipulation by electric field was also achieved in the (Ga,Mn)As magnetic semiconductor. 13 Theoretically, the electric field effect on the MCA was investigated for various free-standing magnetic metal films 10,14-17 and Fe/MgO interfaces.…”
mentioning
confidence: 99%